Diaquabis(2,4-dichloro-6-formylphenolato)zinc(II)–bis(μ-2,4-dichloro-6-formylphenolato)bis[aqua(2,4-dichloro-6-formylphenolato)zinc(II)] (2/1) - Watanabe, Yoshimasa (International Union of Crystallography, 2009)
The crystal of the title compound, [Zn(C(7)H(3)Cl(2)O(2))(2)(H(2)O)(2)](2)·[Zn(2)(C(7)H(3)Cl(2)O(2))(4)(H(2)O)(2)], consists of monomeric and dimeric Zn(II) complexes. Both complexes afford a six-coordinated coordination environment about the Zn atoms with cis-configuration ligands. The deprotonated hydroxy groups of the 3,5-dichlorosalicylaldehyde ligands bridge two metal cations, forming a centrosymmetric dimeric complex. Intermolecular O—H⋯O hydrogen bonding occurs between the coordinated water molecules and deprotonated hydroxy groups in the crystal structure.